PENGARUH KOMPENSASI, DISIPLIN KERJ, DAN MOTIVASI TERHADAP KINERJA PEGAWAI PT MULTI TERMINAL INDONESIA - Deru Pramadhanu Albar (2022)
The Effect of Compensation, Work Discipline, and Motivation on Employee Performance at Pt Multi Terminal Indonesia By Deru Pramadhanu Albar ABSTRACT This study is a quantitative study that aims to determine whether there is an effect of compensation, work discipline, and motivation on the performance of PT Multi Terminal Indonesia employees. This study used 67 respondents, the sampling technique used a random sampling technique. The hypothesis in this study, namely to determine the effect either partially or simultaneously of the variables X and Y, so that the tests used are the coefficient of determination test, f test and t test. Furthermore, the research results obtained, namely: (1) compensation has a positive and significant effect on employee performance, (2) work discipline has a positive and significant influence on employee performance, (3) motivation has a positive and significant influence on employee performance, (4) compensation, work discipline, and motivation simultaneously have a significant effect on employee performance PT Multi Terminal Indonesia. Keywords : Compensation, Work Discipline, Motivation, and Employee Performance